Analytical Study of Generation, Composition, And Potential For Waste Recycling - Oka Lesmana S; Fajrina Hidayati (Chakra Brahmanda Lentera Institute, 2024)
Background: Waste is still a serious problem globally. Accumulated and poorly managed waste becomes a reservoir for disease vector animals in the environment. Sources of waste include home activities, offices, schools, campuses, industry, and other public places Methods: This research was conducted using a survey, which took samples from several research locations and used observation sheets as a data collection tool. In this research, measurements and recording were carried out to calculate the generation and composition of waste in the campus environment. Results: The research results describe the generation and composition of waste at one of the survey locations, Unja Sports Hall. The survey, conducted for five days, yielded results that included the average waste generation per day being 2.5 L and most food waste. The average dry waste generation is 5.3827 L consisting of 6.84% paper, 73.44% plastic, 2.15% badminton cocks and 17.58% styrofoam. The waste with the most significant recycling potential is dry, namely 76%, including 8.87% paper, 66.27% plastic, and 0.41% cans. Apart from that, wet waste also has the potential to be recycled as compost, namely 24.58%, consisting of 17.08% food waste and 7.77% yard waste. Based on organic and inorganic waste, organic waste has a recycling potential of 24.58%, and inorganic waste has a recycling potential of 66.27%. Conclusion: Organic waste that can be recycled consists of food and yard waste, and inorganic waste consists of plastic, paper, and cans. This waste recycling process will produce a craft that has selling value. Before carrying out the recycling process, a waste sorting process is carried out according to specific criteria.